Penyuluhan Kesehatan Tentang KB Dan Alat Kontrasepsi Di Kelurahan Sawah Lebar RT 24 Kecamatan Ratu Agung Kota Bengkulu Tahun 2024 - Pratiwi, Nindya Anggi; Invaka , Vela; Hadara, Hadara; Furiyanti, Murdani; Tania, Rilda Dwi; Prasetyo, Lupus Tri; Sari, Delvi Kembang; Yuliani Y , Reza; Sari , Helpi Kurniawan; Ramdan , Asrial; Aurosi, Miftakhul; Sari , Lezi Yovita; Wara , Gina (Jurnal Karya Nyata Pengabdian, 2024)
Indonesia, as a developing country with a large population, is greatly helped by the presence of methods of contraception to suppress population and improve women's health. The types of salted contraceptives ranging from MKJP and Non-MKJP. Each type of contraceptive has its advantages and disadvantages and each has its individual suitability and suitability for each woman. The provision of comprehensive information is one of the key factors in the selection of contraceptive tools. Provision of information related to contraceptives and their types as well as health detection in women after childbirth is optimized to increase the coverage of active CB participants and reduce the high-risk groups that should not use certain methods of contraception. The method of this activity is conducted with interviews to see if the participants know and understand the material.The conclusion of this study Overall, this community service program has succeeded in achieving its primary objective in raising public awareness of the importance of UN in the family to maintain a lifestyle and economic balance.